2007
DOI: 10.1021/mp7001076
|View full text |Cite
|
Sign up to set email alerts
|

Double-Stranded RNA Homopolymer Poly(rC)·Poly(rG) for a New pH-Sensitive Drug Carrier

Abstract: Double-stranded RNA homopolymer poly(rC).poly(rG) has been used as a new pH-sensitive drug carrier. The poly(rC).poly(rG) had proton buffering capacity around pH 6, owing to protonation of cytosine, as determined by acid-base titration. By circular dichroism measurement, the protonation caused conformational change of the RNA. The poly(rC).poly(rG) and doxorubicin (Dox), as an anticancer drug, formed the complexes which released the drugs at endosomal pH. The resulting complex exhibited higher anticancer activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The present study demonstrates the proof of concept for a combined chemoimmunotherapy approach. Entrapping or conjugating drugs to synthetic biocompatible polymeric carriers or natural polymers such as RNA ensures efficient drug delivery and, in turn, minimizes the adverse toxicity of drugs. In this regard, we used a plasmid as a drug carrier in that it can load large amounts of doxorubicin without need of chemical conjugations or treatments and form a stable complex. We found that the stability of naked plasmid was markedly enhanced in the form of complex with doxorubicin as revealed in the in vitro serum stability assay and in the in vivo pharmacokinetics data.…”
Section: Discussionmentioning
confidence: 99%
“…The present study demonstrates the proof of concept for a combined chemoimmunotherapy approach. Entrapping or conjugating drugs to synthetic biocompatible polymeric carriers or natural polymers such as RNA ensures efficient drug delivery and, in turn, minimizes the adverse toxicity of drugs. In this regard, we used a plasmid as a drug carrier in that it can load large amounts of doxorubicin without need of chemical conjugations or treatments and form a stable complex. We found that the stability of naked plasmid was markedly enhanced in the form of complex with doxorubicin as revealed in the in vitro serum stability assay and in the in vivo pharmacokinetics data.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of non-Watson-Crick base pairs in RNA-protein recognition is clearly documented (Hermann and Westhof, 1999;Chandrasekhar and Malathi, 2003). More recently, the potential of the H L -structure of polyC þ G as an efficient drug carrier was proposed (Asayama et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…If a polymer has H + -buffering capacity at endosomal pH as well as drug-loading sites, the design of polymeric drug carriers would be promising; for example, the double-stranded RNA homopolymer poly( R -cytosine)-poly( R -guanine) with H + -buffering capacity at pH ∼ 6, has shown promising results as a new class of pH-sensitive drug carriers owing to the protonation of cytosine [26] .…”
Section: Biologymentioning
confidence: 99%
“…The major drawback in most of these delivery systems is the delivery of active biomacromolecules to the cytoplasm as it is generally hindered by the endosomal-lysosomal barrier. The internalized hydrophilic carrier-drug complex is entrapped in endosomes and is unable to reach the cytoplasmic space [26] .…”
Section: Expert Opinionmentioning
confidence: 99%